Upgrade Games Cognitive And Literacy For Android - Based Kindergarten Children - Febriyanti, Ika; Wahana, Aditya; Syah, Firdiyan (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
The growth of children in kindergarten is crucial for developing their thinking patterns and creativity. Gadgets can influence children's cognitive and literacy abilities, so a cognitive game is needed to help improve these skills. The development of the game uses VAK and IMSDD methods to improve cognitive abilities and literacy better than conventional learning. The alpha testing showed that more than 90% of respondents agreed that the SITEKA game application met their needs and increased children's concentration and learning effectiveness by over 40%